Hubungan suku bunga, inflasi, dan return emiten industri otomotif di Indonesia - Elia Sofila Simarmata; Jili Saisab (Yayasan Widyantara Nawasena Raharja, 2023)
At the beginning of 2023, the condition of the capital market in Indonesia is still colored by the issue of the continuation of the COVID-19 pandemic and information on issues of the global crisis which tends to have an effect of investment uncertainty, especially in the automotive industry. This study uses time series data with an observation period of 1 January 2023 to 30 April 2023. This study finds that the average return on stocks in the automotive industry has a better risk-return tradeoff in April. In addition, it was also found that changes in interest rates from the Central Bank tend not to have an impact on the rate of return on stocks from the automotive industry. This study also finds that changes in the inflation rate tend to be followed by non-unidirectional changes in returns.